(untitled) (Journal of Partial Differential Equations, 2020)
In this paper we study the mixed initial-boundary value problem for inhomogeneous quasilinear hyperbolic systems in the domain D = (t, x) | t ≥ 0, x ≥ 0. Under the assumption that the source term satisfies the matching condition, a sufficient condition to guarantee the existence and uniqueness of global weakly discontinuous solution is given.